Social origin and the financial feasibility of going to university: the role of wage penalties and availability of funding. Issue 11 (2nd November 2019) - Findlay, Jeanette; Hermannsson, Kristinn
ABSTRACT: The evidence on why students from lower social origin are persistently underrepresented in higher education (HE) suggests social, educational and economic factors all play a role. We concentrate on the influence of monetary costs/benefits and how these are influenced by social origin. In particular, we consider the effect of a class-based wage penalty in the labour market and, using evidence from a large-scale survey of Scottish students, we show how the greater financial constraints facing working-class students affects the incentive to participate in HE. Using a simple model of human capital investment, the low rate of working-class participation in HE is shown to be consistent with rational behaviour, i.e. weighing the monetary costs and benefits, participating in HE is a less attractive investment proposition for some students. We conduct simulations which suggest this could be mitigated by generous income-contingent support.